Analisis Pengaruh Service Quality, Perceived Value Dan Institution Image Terhadap Kepuasan Mahasiswa Universitas Bengkulu - Saputra, Kurniawan; Hadi, Effed Darta; Anggarawati, Sularsih (Universitas Bengkulu, 2025)
This research was conducted to obtain an overview of service quality at Bengkulu University by linking it to various aspects as implications of the implementation of quality services. The aim of this research is to analyze the influence of service quality, perceived value, and institutional image on student satisfaction at Bengkulu University. The population of this research is Bengkulu University students from various faculties who have studied for at least 2 semesters (third semester and above). The sampling method that collects data is purposive. The sample size was 268 respondents. The research results found that: 1) Service quality has a positive and significant influence on student satisfaction at Bengkulu University. This means that the better the quality of educational services, the better the satisfaction of Bengkulu University students. 2). Perceived value has a positive influence on student satisfaction at Bengkulu University. This means that if the perceived value increases, student satisfaction will increase. 3). The image of the institution has a positive effect on student satisfaction at Bengkulu University. This means that improving the image of the institution will have an impact on increasing student satisfaction at Bengkulu University. 4). Service quality, perceived value, and institutional image have a positive influence on Bengkulu University student satisfaction.